Development Of Linkage Mechanism For In-Pipe Robot - Megat, Nik Muhammad Ashraf Che (Universiti Sains Malaysia, 2019)
Pipeline inspection works has been done by human to observe and identify any leakage especially in industrial plant, chemical, natural gas and oil rig. This job environment is the most dangerous and high possibility to give hazard for workers in short or long term effect. To encounter this problem, in-pipe inspection robot has been introduced to replace the job and evolved to offer better performance compared with manual inspection. The purpose of this project is to design a in-pipe robot which is capable to move in the pipe and turning in stable condition in the pipe junction with various diameter in the market and industry. The design of robot including the mechanism on how to turn in the corner of the pipe and the area of contact for the robot to keep stable while moving through the pipeline. To make the robot mobile in the pipeline, control system is implemented in the robot’s body to rotate the wheels by using Arduino UNO as a “brain” that transmit electrical supply to locomotion of the robot. After conducting experiment, robot is observed can make turn in the pipe junction and make good mobility in straight pipe. However, suitable material selection at the ball wheels will give different effect towards grip performance on pipe wall. Thus, the suitable material is coating the rubber on ball wheels to ensure better gripping performance. This project can give contribution on the robot’s mechanism to passing through the juction of pipe.